Assessment of the potential of radiography and ultrasonography to record flow dynamics in cohesive sediments (mud) - Brouwers, Bart; van Beeck, Jeroen; Meire, Dieter; Lataire, Evert (Frontiers in Earth Science, 2022)
The possible use of both radiography and ultrasonography to visualise flow dynamics in cohesive sediments, also known as fluid mud, has been assessed. Ultimately, these techniques are intended to enable the application of Particle Image Velocimetry (PIV) in experimental fluid dynamics using such fluid mud. This research takes into account the specific requirements arising from this objective. Those requirements are primarily penetration depth, adequate frame rate and the preference not to seed with tracer particles. The evaluation of both techniques is elaborated in detail based the properties of mud originating from the Port of Zeebrugge (Belgium). The assessment of radiography starts with a chemical element analysis of the fluid mud, the results of which are used to determine the attenuation for high-energy electromagnetic radiation. Using various research software, the maximum thickness of the mud layer could be determined as a function of the maximum recordable flow velocities for different radiation sources. However, for the flow velocities expected in nautical research experiments, these thicknesses proved insufficient. Supplemented by the results of a particle size distribution analysis, it is found that high frequency ultrasound radiation will scatter in mud. In case of a great number of scatterers, the scattered ultrasound waves will interact, eventually resulting in speckle images, which are ideally suited for tracking. These findings were confirmed in a test setup with a standard medical ultrasound scanner. The penetration depth of ultrasonography with standard medical equipment is also limited. However, since ultrasonography is based on reflection, this is less of an issue compared to radiography, for which full penetration of the mud layer is required. Ultrasonography is therefore suggested as the preferred technique for the intended application.Keywords: cohesive sediment, visualization, high opacity, non-transparent, velocimetry, laboratory experiments, fluid dynamics